Community structure of bivalve on seagrass ecosystems in the West Bali National Park area - Sang Ayu Made Putri Suryani; I Wayan Mega Ambaranatha; Ni Made Darmadi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
The waters of Taman Nasional Bali Barat are one of the waters that have abundant diversity of marine ecosystems. Seagrass is an ecosystem that has many benefits for organisms that live in it, one of which is bivalves. Bivalves can be used as jewelry, food sources, and are often used as bioindicators of pollution. Seagrass and bivalves have the same characteristics related to the type of substrate that serve as habitat and need each other in both growth and reproduction processes. This study aims to determine the condition of seagrass cover, the abundance and diversity of bivalves, and the relationship between seagrass cover and bivalves density. This research was conducted at 3 stations, namely Karang Sewu, Terima Bay, and Labuhan Lalang in August 2020. This research was conducted using survey method and sampling technique using a purposive sampling method. To determine the relationship between seagrass cover and bivalves density using a linear regression test. The results showed that the seagrass cover at the three stations was 31.04%, 50.46%, and 50.68%. Bivalves density in Karang Sewu Bay was 29.8% Aomalodiscus squamosus, Terima Bay with 50% Pinna bicolor, and Labuhan Lalang with 30.4% Trachycardium flavum and Pinna bicolor. Based on the linear regression test, it showed a significant value 0.5 which means that there is the relationship between seagrass cover and the density of bivalves found in the waters of Taman Nasional Bali Barat.Keywords:seagrassbivalvesdensityecosystemcommunity structure